Dispersal dynamics of white-tailed deer in human-altered landscapes and implications for disease risk. - Tayler N LaSharr; Marie L J Gilbertson; Kelsie LaSharr; Michelle Carstensen (PLoS ONE)
Animal dispersal and migration can play critical roles in population dynamics and species distribution, and these behaviors often are influenced by their environment. The conversion from natural habitats to agricultural lands has altered over 40% of terrestrial surfaces and many wildlife species now inhabit landscapes that are fragmented or heavily composed of agriculture. Understanding how habitat drives patterns of dispersal or migration is of critical importance to population management, particularly in environments that may be changing rapidly with human presence and when considering emerging disease threats. We evaluated how habitat and agriculture in and around white-tailed deer natal ranges in southeastern Minnesota, USA influenced both the probability of dispersal and migration events and the distance animals traveled during those events. Counter to our predictions, we found no evidence that agriculture in the natal range influenced the probability that white-tailed deer would disperse or migrate. Sex, however, played an important role in shaping movement behaviors-compared with resident deer, males were 2.7 times more likely to disperse and 5.2 times less likely to migrate than females. Moreover, while agriculture did not influence the probability of a dispersal event occurring, it did influence the distance traveled with deer dispersing farther in areas with more agriculture and avoiding agriculture during dispersal events. Our results provide insight into the influence of habitat on key movement behaviors that may be extremely important for population management, especially in areas that may have a high prevalence of infectious disease.